Intrafamily Entrepreneurship: The Formation and Membership of Family Entrepreneurial Teams - Discua Cruz, Allan; Howorth, Carole; Hamilton, Eleanor (Entrepreneurship Theory and Practice, 2013)
Family entrepreneurial teams are groups of related individuals who engage in entrepreneurship. Entrepreneurial teams studies emphasize the resources that members bring to the team. Family business studies suggest that relationships and social theories are important. Social capital explains the formation and composition of family entrepreneurial teams (FETs). Analysis is of case studies of FETs based in Honduras. A shared commitment to entrepreneurial stewardship of the family's assets underpins formation of FETs. Trust and shared values were important for membership. This study highlights that families are not internally consistent, and family ties are not equally strong.